Analisis Hakikat Pembelajaran Sejarah Kebudayaan Islam dalam Pembentukan Karakter dan Kesadaran Historis Peserta Didik - Dian Zulfa Kameliatul Huda; Adhelia Az’zahra Salsabila; Ibnu Arfah; Febri Parlentino; Afiyatun Kholifah (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2026)
This study aims to analyze the essence of Islamic Cultural History (ICH) learning in shaping students’ character and historical consciousness. ICH learning serves not only as a medium for delivering knowledge about Islamic historical events and figures but also as a means of internalizing moral, religious, and social values relevant to students’ lives. This research employs a library research method by reviewing various literature sources, including books, journals, and scholarly publications related to ICH learning, character education, and historical consciousness. The findings indicate that ICH learning plays a strategic role in character formation by instilling values such as religiosity, honesty, responsibility, tolerance, and a spirit of learning through the exemplary lives of Islamic figures. Furthermore, ICH learning contributes to the development of historical consciousness by enabling students to understand the relationship between the past, present, and future and to draw meaningful lessons from historical events. Therefore, ICH learning should be developed through contextual, reflective, and value-oriented approaches to foster students with strong character and a well-developed sense of historical awareness.